(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
As a result of the development of modern automation, the expediency of using small devices for synchronous vector measurements in 0.4-35 kV networks - ACONaEM sensors (automatic control of normal and emergency modes) has been proved, which allows you to calculate the required operating parameters based on current and voltage synchro vectors.